Pembelajaran Pendidikan Pancasila dan Implementasi Nilai Demokrasi di Sekolah Dasar - Kristiani, Hilda; Ramadhani, Suci; Sitompul, Yohana Melfrida (Yayasan Daarul Huda Kruengmane, 2024)
Education is a right and a need for every individual human being. Education is always developing to be better, as is the application of democratic values. Education in learning at school is also experiencing development to be better and carries a concept that creates freedom for students to give opinions, give rebuttals without looking at race, ethnicity, religion and class. The purpose of making this article is because the researcher wants to inform about the importance of democratic values in the elementary school environment which is carried out through Pancasila education learning. This research uses a library study method where data is obtained from journals, articles and websites available on the internet and analyzed using a qualitative approach using data analysis techniques through four stages, namely searching for data, reducing data, presenting data and drawing conclusions. The research results show that students are currently not only used as learning objects but also as subjects who are involved in discussions during the learning process. Therefore, it is hoped that teachers will be able to create a democratic learning environment for students.